1977
DOI: 10.1148/124.2.493
|View full text |Cite
|
Sign up to set email alerts
|

The Significance of Residual Disease after External Irradiation of Squamous-Cell Carcinoma of the Oropharynx

Abstract: 366 patients with squamous-cell carcinoma of the oropharynx treated by external irradiation were studied to see whether residual disease at the end of treatment influences control. The frequency of recurrence was found to be significantly greater when residual disease was present. When the total dose was determined by the degree of regression of the primary lesion during treatment rather than the initial tumor volume, recurrence was significantly more frequent. Forcing the dose beyond a level suitable for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1983
1983
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Previous studies have revealed that significant anatomic changes occur during IMRT in patients with head and neck cancer, including weight loss and shrinkage of the primary tumor and nodal mass. 5 , 6 , 8 , 10 Barker et al found that the gross target volumes and parotid glands decreased in volume at a median rate of 1.7% to 1.8% and 0.6%, respectively, per day in the course of radiotherapy. 6 Furthermore, many studies have shown that anatomical changes may influence the dose distribution of target volumes and OARs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have revealed that significant anatomic changes occur during IMRT in patients with head and neck cancer, including weight loss and shrinkage of the primary tumor and nodal mass. 5 , 6 , 8 , 10 Barker et al found that the gross target volumes and parotid glands decreased in volume at a median rate of 1.7% to 1.8% and 0.6%, respectively, per day in the course of radiotherapy. 6 Furthermore, many studies have shown that anatomical changes may influence the dose distribution of target volumes and OARs.…”
Section: Discussionmentioning
confidence: 99%
“… 4 Small variables, including external daily setup variations and internal changes in the anatomy during the IMRT course, could greatly alter the actual dose delivery. 4 Previous studies have revealed that significant anatomic changes, such as weight loss, occurred in the course of IMRT, 6 , 7 , 8 , 9 , 10 which led to significant clinical consequences, including underdose of target volumes and overdose of normal tissues.…”
Section: Introductionmentioning
confidence: 99%